2020
DOI: 10.1002/jcla.23621
|View full text |Cite
|
Sign up to set email alerts
|

Research on the circular RNA bioinformatics in patients with acute myocardial infarction

Abstract: Objective Through the detection of circular RNA (circRNA) using expression profiling chips, we searched for circRNAs related to acute myocardial infarction (AMI) and explored their relationship and possible mechanisms with AMI. Method The study subjects included 3 AMI patients and 3 controls, and circRNA expression profiling analysis was performed using a microarray gene chip to identify circRNAs with large differences in expression between groups and to construct a circRNA‐miRNA network. Results Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…(Wuweizi) and Shell of Trichosanthes kirilowii (Gualoupi). Unlike the synthetic drugs, which generally produce their efficacy based on the theory of one drug and one target, the efficacy of TCMs relies on the comprehensive effects of multiple compounds, multiple targets, and multiple pathways 16 . Therefore, it is difficult to discover the key components and targets of Yixinyin in the treatment of MI from the molecular level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wuweizi) and Shell of Trichosanthes kirilowii (Gualoupi). Unlike the synthetic drugs, which generally produce their efficacy based on the theory of one drug and one target, the efficacy of TCMs relies on the comprehensive effects of multiple compounds, multiple targets, and multiple pathways 16 . Therefore, it is difficult to discover the key components and targets of Yixinyin in the treatment of MI from the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have studied the pathogenesis of MI in order to find more available treatments 16 . Network pharmacology is a commonly-used technology for analyzing the mechanism of traditional Chinese medicine from the compound molecules and targets 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been commonly acknowledged that circRNAs are the key regulators in MI. 12 , 17 Hsa_circ_0000848 has been reported to be involved in trophoblast cell proliferation, migration, and apoptosis through interacting with miR-6768-5p. 18 Moreover, it has been reported that hsa_circ_0000848 can promote the cell proliferation of glioma by upregulating PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al. 139 identified 650 circRNAs, including 535 upregulated circRNAs and 115 downregulated circRNAs, that were differentially expressed in AMI patients compared with control subjects. Myocardial expression of circRNAs is very high in AMI patients, and due to the stability and conserved nature of circRNAs, they are likely to be robust and sensitive biomarkers for MI.…”
Section: Circrnas As Diagnostic and Prognostic Biomarkers For MImentioning
confidence: 99%